Sociocultural Features of Civic Education of Students in the "School–Mahalla" System in Uzbekistan (Uzbekistan Open Conference, 2025)
The article analyzes the sociocultural features of civic education of students within the “School–Mahalla” system in Uzbekistan. It highlights the significance of this model as an integrative form of cooperation between school, family, and local community in postmodern society. The study discusses the influence of sociocultural transformations on the formation of civic identity and educational practices promoting national and global citizenship. The “School–Mahalla” model is presented as a sustainable educational mechanism that preserves traditional values while fostering adaptation to contemporary global changes.